Improving Honest Attitude and Learning Outcomes Human Excretion System using Discovery Learning - Nursaadah, Siti; HP, Mulyadi (Universitas Negeri Semarang, 2022)
The purpose of this research is to determine the improvement of honest attitude and learning result of human excretion system material using the discovery learning model in class VIII H SMP 5 Semarang semester 2 of 2018/2019. This research is a classroom action research. These research subjects are all students of class VIII H SMP 5 Semarang consisting of 32 people. This research was conducted with pre-cycle, cycle I, and cycle II stages. Data collection techniques are carried out by means of documentation techniques in the initial conditions, observation techniques, and test techniques in the first cycle and second cycle. Data analysis techniques by comparing the variables of honest attitude and learning outcomes in the initial conditions with conditions in the first cycle and second cycle. The results showed that there was an increase in students' honesty in the pre-cycle stage (73.68%), the first cycle (82.81%), and the second cycle (88.28%). There was an increase in learning outcomes before the action (pre-cycle) (59%), cycle I (79.86%), and cycle II (87.06%). Improving students' honesty and learning outcomes becomes a consideration for teachers to use discovery learning models and becomes information material for schools to prepare media or learning materials for discovery learning models.